Stand Up and Speak: Implementing the ‘Qum Takallam’ Method to Foster Arabic Oral Expression - Segaf Baharun; Nur Hanifansyah; Nur Aunie Batrisya (Universitas Ahmad Dahlan, 2026)
The mastery of Arabic mahārah kalām (speaking skills) remains one of the most challenging aspects of foreign language pedagogy, especially in non-Arabic speaking contexts where learners often possess adequate knowledge of vocabulary and grammar but struggle with fluency, confidence, and spontaneous oral performance. This study introduces and evaluates the Qum Takallam method, a pedagogical approach that requires students to “stand up and speak” in Arabic for ten minutes on a chosen or spontaneous topic. Conducted at Darullughah Wadda’wah Boarding School in Pasuruan, Indonesia, the research employed a mixed-methods design involving 30 intermediate-level male students. Data were collected through pre- and post-tests of oral expression, classroom observations, and semi-structured interviews, and analyzed using paired sample t-tests and thematic analysis. The quantitative results demonstrated significant improvements across fluency, vocabulary, and confidence, with large effect sizes, while accuracy improved more modestly. Qualitative findings revealed that the method reduced anxiety, fostered autonomy, and encouraged peer learning, although some students continued to struggle with coherence and persistent grammatical errors. These outcomes align with previous research on communicative and experiential learning yet extend the discussion by situating spontaneous stand-up speaking within Arabic pedagogy. Overall, the Qum Takallam method provides a simple, low-cost, and sustainable strategy for integrating structured oral practice into Arabic curricula. By balancing linguistic creativity with communicative competence, it contributes to developing confident and expressive Arabic speakers, while highlighting the need to complement fluency-focused approaches with explicit grammar instruction.